2011
DOI: 10.1055/s-0031-1284234
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Near-Infrared Spectroscopy Tissue Oximetry for Monitoring Autologous Free Tissue Breast Reconstruction

Abstract: Free flap monitoring typically requires specialized nursing that can increase medical costs. This study uses near-infrared spectroscopy (NIRS) tissue oximetry to monitor free tissue breast reconstruction. We hypothesize this practice will reduce medical costs by eliminating the need for specialized nursing. From August 2006 to January 2010, women undergoing unilateral free tissue breast reconstruction were enrolled and admitted postoperatively to either the surgical intensive care unit (ICU) or floor. Each und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 7 publications
(8 reference statements)
0
57
2
Order By: Relevance
“…38,[110][111][112] Furthermore, NIRS can eliminate the need for a specialized intensive nursing care and, thus can reduce the cost. 113 There have been 3 comparative studies evaluating the combination of NIRS and clinical monitoring against clinical monitoring alone. 33,34,39 All 3 studies reported high flap salvage rates (94%, 100%, and 100%, respectively), but only 2 trials showed statistical significance.…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…38,[110][111][112] Furthermore, NIRS can eliminate the need for a specialized intensive nursing care and, thus can reduce the cost. 113 There have been 3 comparative studies evaluating the combination of NIRS and clinical monitoring against clinical monitoring alone. 33,34,39 All 3 studies reported high flap salvage rates (94%, 100%, and 100%, respectively), but only 2 trials showed statistical significance.…”
Section: Clinical Monitoringmentioning
confidence: 99%
“…The current costs for a tissue oximetry probe are approximately $700 to $1200, with potential additional costs for the consoles of over $30,000. 14,29 One fiberoptic probe is required for each flap and cannot be resterilized to be used on another patient. However, it can be argued whether the cost of the monitoring technology outweighs the cost of a potential complication and its resulting sequelae.…”
Section: Common Pitfallsmentioning
confidence: 99%
“…Pelletier et al demonstrated an average reduction of $1937 per free flap breast reconstruction patient when monitored on the surgical floor instead of the intensive care unit with the use of tissue oximetry monitoring. 29 To date, our postsurgery protocol is still not dependent on tissue oximetry alone. Instead, it is used as an adjunct to clinical monitoring and routine Doppler assessment with the intention of earlier recognition of flap compromise.…”
Section: Common Pitfallsmentioning
confidence: 99%
“…69 Keller 7 examined the use of ViOptix on breast reconstruction free flaps and concluded that by measuring tissue oxygen saturation and its changes over time, ViOptix could predict vascular complications before the onset of clinical changes—allowing intervention and salvage of every flap in his study. Pelletier et al 10 reached similar conclusions, while also showing that the ViOptix system is a cost-effective flap monitoring device. Given that prompt and accurate recognition of vascular occlusion leads to higher flap salvage rates, the ViOptix system is a useful and economical addition to the arsenal of flap monitoring options.…”
Section: Discussionmentioning
confidence: 65%